2021
DOI: 10.1021/acscatal.0c04777
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Allylic Amine Synthesis Enabled by the Enantioselective CpXRh(III)-Catalyzed Carboaminations of 1,3-Dienes

Abstract: Considering the importance of the chiral allylic amine structural motif and the rarity of synthetic methods toward their construction, herein, we report a Cp X Rh(III)-catalyzed enantioselective intermolecular carboamination of 1,3-dienes via N-phenoxy amides-derived intermolecular aryl C−H activation and intramolecular amide transfer. The methodology enables the direct synthesis of a variety of chiral allylic amines with the embedment of phenol functionalities and proceeds under mild conditions with sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 103 publications
0
20
0
Order By: Relevance
“…Taken together, these results provided adequate evidence to support a N−Rh bond formation initiated C−H activation/regioselective alkyne insertion reaction path. Interestingly, the coupling of 1 a with (prop‐2‐yn‐1‐yloxy)benzene led to the formation of C−H alkenylation product 11 with the retention of ‐ONHAc ODG instead of previously reported [3+2] annulation 4t or carboamination [4a,12] products (Scheme 4e), implying that the coordination effect of the propargylic oxygen with the Rh‐center should be involved for tuning the reaction chemoselectivity.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Taken together, these results provided adequate evidence to support a N−Rh bond formation initiated C−H activation/regioselective alkyne insertion reaction path. Interestingly, the coupling of 1 a with (prop‐2‐yn‐1‐yloxy)benzene led to the formation of C−H alkenylation product 11 with the retention of ‐ONHAc ODG instead of previously reported [3+2] annulation 4t or carboamination [4a,12] products (Scheme 4e), implying that the coordination effect of the propargylic oxygen with the Rh‐center should be involved for tuning the reaction chemoselectivity.…”
Section: Resultsmentioning
confidence: 82%
“…Further screening of different bases showed that Zn(OAc) 2 was optimal, while other bases gave less satisfactory yields or led to the dimerization of 2 a (Table 1, entries 6-9). The examination of other Rh(III) catalysts resulted in inferior efficiency, and no reaction occurred under Ir(III)-or Ru(II)catalytic system (Table 1, entries [10][11][12][13][14]. After a number of trials to screening several experimental parameters including additives, catalyst loading, the reaction temperature and the proportion of substrates (see Table S1 in the Supporting Information for details), we were pleased to identify the optimized conditions and afford the desired cyclization product 3 aa in 63 % isolated yield (Table 1, entry 15).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of the coupling of N ‐phenoxycarboxamide was also briefly explored. A rhodacycle 71 was prepared by following a recent report [24] (Scheme 7). Complex 71 was designated as a catalyst for the coupling of N ‐phenoxyisobutyramide and alkyne 33 , from which the coupled product 59 was isolated in 65 % yield and 98 % ee .…”
Section: Resultsmentioning
confidence: 99%
“…Despite the reports on racemic systems of migration of an oxidizing directing group, [19, 21d] very few asymmetric systems have been developed. Thus, Cramer [23] and Yi [24] accomplished Rh/Co‐catalyzed asymmetric coupling of N ‐phenoxyacetamides with olefins/dienes through migration of the amide group. In case of migration of an electrophilic directing group, [20–22] no asymmetric system has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…8 Encouraged by this progress, we assumed that the selective cleavage of the N–O bond in the isoxazolone motif followed by a facile decarboxylation process might yield the enamine or imine intermediate, which could be easily triggered by electrophiles or nucleophiles. Therefore, in continuation of our interest in developing novel external oxidant free C–H functionalization reactions, 9 we would like to disclose herein the Rh( iii )-catalysed cascade C–H imidization/cyclization of N -methoxybenzamides with isoxazolones for the direct and efficient construction of dihydroquinazolin-4(1 H )-one framework (Scheme 1c), in which isoxazolone acted as an imidizating reagent with the release of one molecule of CO 2 . Combined computational and experimental studies probed the detailed cascade C–H activation/amination/isomerization/intramolecular cyclization sequence involving the distinctive Rh nitrenoid and imine species as active intermediates.…”
mentioning
confidence: 99%